Motivation, Compensation And Discipline On Employee Performance At The Population And Civil Records Office (Disdukcapil) Padang City - M. Iqbal Jafri; Riri Mayliza (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of motivation, compensation and discipline on employee performance at the Padang City Population and Civil Registry Service (Disdukcapil). This type of research is quantitative research. The sample consisted of 75 employees of the Padang City Population and Civil Registry Service (Disdukcapil) using total sampling. The data analysis used is multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results of the research show that the motivation and compensation variables partially have a positive and significant effect on employee performance at the Padang City Population and Civil Registry Service (Disdukcapil). Meanwhile, the discipline variable partially has no effect on employee performance at the Padang City Population and Civil Registry Service (Disdukcapil).